1966
DOI: 10.1113/jphysiol.1966.sp008024
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological studies on feline Betz cells

Abstract: 4. The significance of these results is discussed in relation to the possible synaptic or non-synaptic action of acetylcholine upon cortical neurones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
1

Year Published

1967
1967
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(62 citation statements)
references
References 31 publications
6
55
1
Order By: Relevance
“…In addition, in the olfactory cortex it has been shown that general anaesthetics, including pentobarbitone, depress both excitatory synaptic transmission and the sensitivity of neurones to ionophoretically-applied glutamate (Richards et al, 1975;Richards & Smaje, 1976). Similar results have been reported for the action of barbiturates on the glutamate sensitivity of neurones in the cat neocortex (Crawford & Curtis, 1966). Since these early studies it has become clear that glutamate acts on two major classes of receptor: ionotropic receptors which are integral parts of ion channels and metabotropic receptors which activate second messenger systems.…”
Section: Introductionsupporting
confidence: 75%
“…In addition, in the olfactory cortex it has been shown that general anaesthetics, including pentobarbitone, depress both excitatory synaptic transmission and the sensitivity of neurones to ionophoretically-applied glutamate (Richards et al, 1975;Richards & Smaje, 1976). Similar results have been reported for the action of barbiturates on the glutamate sensitivity of neurones in the cat neocortex (Crawford & Curtis, 1966). Since these early studies it has become clear that glutamate acts on two major classes of receptor: ionotropic receptors which are integral parts of ion channels and metabotropic receptors which activate second messenger systems.…”
Section: Introductionsupporting
confidence: 75%
“…As anaesthetics do not alter the coupling between the population e.p.s.p. and the discharge of the pyramidal cells, this depression is not the result of e a generalized increase in the resting membrane permeability to potassium or chloride such as that seen following the iontophoretic application of 2, 4 dinitrophenol to cortical neurones (Godfraind, Krnjevi6 & Pumain, 1970 In contrast to the other anaesthetics studied, halothane did not depress the glutamate-sensitivity of cortical neurones until relatively high concentrations were reached (> 1%), whereas synaptic transmission became depressed at much lower concentrations (> 0.4%) (Richards, 1973a Crawford & Curtis (1966) and Johnson, Roberts & Straughan (1966) found that systemic administration of barbiturates depressed the sensitivity of cortical neurones to iontophoretically-applied glutamate and DL-homocysteic acid. Crawford (1970), working with the cerveau isole preparation of the cat, found that halothane (< 1.5%) had no effect on the response of cells in the cat pericruciate gyrus but he also reported that methoxyflurane and trichloroethylene were without effect.…”
Section: Discussionmentioning
confidence: 96%
“…In these experiments, the 'control barrel' contained NaCl only as in the bulk of the experiments of Krnjevi6 & Phillis (1963a, b) and Crawford & Curtis (1966). Apparent differences between the 5-HT salts should thus be due to differences between the cation and anion species associated with 5-HT in the salt.…”
Section: Methodsmentioning
confidence: 99%